Investigating the Performance of Perovskite Solar Cells Using Nickel Oxide and Copper Iodide as Ptype Inorganic layers by SCAPS-1D Simulation - Olayinka M Jimoh; Ikechiamaka N Florence; Akinsanmi Akinbolati; Chima Nnachi; Clement Ajani; Philibus M Gyuk; Suleiman Magaji; Eli Danladi (Physics Access, 2022)
Lead-based perovskite solar cells (PSCs) have drawn much research attention over the years due to their impressive light-to-power conversion efficiency (PCE), low temperature with easy manufacturing, tolerance to defects, high absorption coefficient and low cost. In this paper, the effect of absorber thickness, absorber band gap, absorber doping concentration, and electron transport material (ETM) thickness of PSC with two inorganic hole transport materials (HTM) was investigated using one-dimensional solar capacitance simulation (SCAPS-1D) software. Results obtained indicates that solar cell containing CuI as HTM performed better than that with NiO. A power conversion efficiency of 16.65%, fill factor (FF) of 82.43%, current density (Jsc) of 24.83 mA/cm2 and voltage (Voc) of 0.83 V were obtained for CuI with an enhancement of 1.15 times in PCE, 1.10 in Jsc and 1.17 in FF over the initial device and PCE of 15.74%, FF of 74.69 %, Jsc of 27.22 mA/cm2 and Voc of 0.77 V for NiO with an enhancement of 1.20 times in PCE, 1.25 times in Jsc and 1.15 in FF when compared with the initial device. The result therefore, shows that CuI as HTM performed better than NiO and implies that critical selection of the absorber parameters is a very key factor to enhance solar cell devices.